2006
DOI: 10.2139/ssrn.933601
|View full text |Cite
|
Sign up to set email alerts
|

Baby Boomer Retirement Security: The Roles of Planning, Financial Literacy, and Housing Wealth

Abstract: This paper compares wealth holdings across two cohorts of the Health and Retirement Study: the early Baby Boomers surveyed in 2004, and individuals in the same age group in 1992. We find that levels and patterns of total net worth have changed relatively little over time, though Boomers will rely more on housing equity than their predecessors. Most importantly, planners in both cohorts approached retirement with much higher wealth levels and display higher financial literacy than non-planners. Instrumental var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

41
593
5
37

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 419 publications
(676 citation statements)
references
References 13 publications
41
593
5
37
Order By: Relevance
“…Lusardi (2008) argues ignorance about basic financial concepts is linked to lack of retirement planning and lack of wealth. The importance of retirement planning is further emphasised by Lusardi and Mitchell (2007a) who find planners arrive close to retirement with much higher wealth levels and display higher financial literacy than non-planners. Focusing on gender issues, Lusardi and Mitchell (2008) also find that older women display much lower levels of financial literacy than the older population as a whole.…”
Section: Planning Constructsmentioning
confidence: 99%
“…Lusardi (2008) argues ignorance about basic financial concepts is linked to lack of retirement planning and lack of wealth. The importance of retirement planning is further emphasised by Lusardi and Mitchell (2007a) who find planners arrive close to retirement with much higher wealth levels and display higher financial literacy than non-planners. Focusing on gender issues, Lusardi and Mitchell (2008) also find that older women display much lower levels of financial literacy than the older population as a whole.…”
Section: Planning Constructsmentioning
confidence: 99%
“…The effectiveness of such programs have been evaluated through, among others, individuals" portfolio diversification [4], extents of the disposition effect [5] and retirement planning [6]. The main problem associated with low level of financial literacy is that individuals can suffer credit problems which may lead to bankruptcy.…”
Section: A Financial Literacymentioning
confidence: 99%
“…Note that the quiz only contains 10 questions which may not be exhaustive but deemed sufficient to measure the literacy level for our study since the targeted respondents are common working individuals. These literacy measures can be regarded as Tier 1 literacy or basic financial literacy [6]. In hire purchase financing, the owner of the car is ______.…”
Section: B Construct Operationalizationmentioning
confidence: 99%
“…[17][18][19] Looking at the racial dynamics of these disparities, researchers using post-2000 data sets find that black households nearing retirement have a median net worth of $27,000, compared to $198,000 for whites in the same age group. 20 Another study using data from 1998 and 2001 found that reserves for financial emergencies were much lower for black than for white households. 21 Shapiro, Meschede, and Sullivan 22 reported that the median wealth gap between white and African American families in 1984 would pay 3 years tuition for one child at a public institution.…”
Section: Health Inequality and Housingmentioning
confidence: 99%